Comparative Analysis of the Implementation of Management Functions in Community Health Centers (Puskesmas) Accredited as Paripurna and Madya in Kolaka Regency - Mauliah, Failal Ulfi; Asriati, Asriati; Zainuddin, Asnia (Journal of Engineering Science and Technology Management (JES-TM), 2025)
This study aims to analyze the differences in the implementation of management functions between community health centers (Puskesmas) accredited as Paripurna and those accredited as Madya in Kolaka Regency. A descriptive qualitative approach was employed using a case study method involving six Puskesmas—three with Paripurna accreditation and three with Madya accreditation. Data were collected through in-depth interviews, participatory observation, and document review. The research focused on three main management functions of Puskesmas: planning (P1), organizing and implementation (P2), and supervision, control, and performance evaluation (P3). The findings show that Paripurna Puskesmas excel in strategic planning that involves cross-sector participation and data-based decision-making. The P2 function is optimally implemented through regular coaching, inter-unit coordination, and the use of information technology. In the P3 aspect, Paripurna Puskesmas demonstrate stronger internal supervision systems and periodic evaluations of service quality. In contrast, Madya Puskesmas still face challenges such as limited human resources, lack of managerial support, and low integration of information systems. The study emphasizes that synergy among human resources, organizational culture, leadership, and local government support is a key factor for effective management function implementation in Puskesmas. The practical implication of these findings highlights the importance of structural interventions and system strengthening to enhance the readiness of Madya Puskesmas toward Paripurna accreditation. This study also contributes to the development of evidence-based primary health care policies at the regional level.